Infant gut microbiome composition is associated with non-social fear behavior in a pilot study - Alexander L. Carlson (Nature Portfolio, 2021)
Experimental manipulation of the gut microbiome in animal models impacts fear behaviours. Here, the authors show in a pilot study that features of the human infant gut microbiome are associated with non-social fear behaviours during a laboratory based assessment.